2012
DOI: 10.26848/rbgf.v5i2.232796
|View full text |Cite
|
Sign up to set email alerts
|

Análise de Detecção De Tendências no Padrão Pluviométrico na Bacia Hidrográfica do Rio Capibaribe

Abstract: Este trabalho tem como objetivo avaliar os índices de detecção de mudanças climáticas na bacia do Rio Capibaribe localizada no Estado de Pernambuco. Nesse contexto, este trabalho propôs investigar uma possível alteração no ciclo hidrológico, por meio das análises das tendências dos índices de detecção de mudanças climáticas, obtidos a partir da precipitação diária de postos pluviométricos espalhados por toda a bacia hidrográfica. Foram selecionados dados de oito postos pluviométricos, no período 1963 a 2008, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…O cenário climático brasileiro acompanha a mesma tendência de aquecimento global, em que as mudanças mais significativas são no aumento de temperatura, modificações nos padrões de chuvas e alterações na distribuição de extremos climáticos, tais como secas, enchentes e inundações (Assis et al, 2012). Uma avaliação da variabilidade climática, ao longo do tempo no Brasil, mostra que, dependendo da região analisada, podem ocorrer alterações contínuas ou ciclos bem demarcados dos elementos meteorológicos, como a temperatura e a precipitação (Pinto et al, 2003).…”
Section: Introductionunclassified
“…O cenário climático brasileiro acompanha a mesma tendência de aquecimento global, em que as mudanças mais significativas são no aumento de temperatura, modificações nos padrões de chuvas e alterações na distribuição de extremos climáticos, tais como secas, enchentes e inundações (Assis et al, 2012). Uma avaliação da variabilidade climática, ao longo do tempo no Brasil, mostra que, dependendo da região analisada, podem ocorrer alterações contínuas ou ciclos bem demarcados dos elementos meteorológicos, como a temperatura e a precipitação (Pinto et al, 2003).…”
Section: Introductionunclassified
“…The same results were found by Araújo & Brito (2011), who observed positive trend for the Rx1day index and negative trend for the Rx5day index. However, Assis et al (2012) found decreasing trends for the Rx1day and Rx5day indexes. Rx5day is an indicator for the possibility of landslide occurrence, as it represents the maximum rainfall accumulated in 5 consecutive days.…”
Section: Resultsmentioning
confidence: 83%
“…Some of these events causes harm to society, such as significant economic losses, which can cause contamination, threat to public health and even death. For the Northeastern region of Brazil, studies such as those by Araújo and Brito (2011); Assis et al, (2012); Souza and Azevedo (2012) and Wanderley et al (2014) have shown changes in rainfall distribution, some of these changes with statistical significance.…”
Section: Introductionmentioning
confidence: 94%
“…An increasing trend on the global average temperature of 0.85°C, was observed, between 1880 and 2012, and in extreme rainfall events, which are more intense and frequent at tropical humid places and medium latitudes (IPCC, 2014). In Brazil, the climate scenario is similar to the global trend, with significant changes in temperature, rainfall patterns, and climatic extremes such as droughts and floods (ASSIS et al 2012).…”
mentioning
confidence: 94%